2020
DOI: 10.2196/20979
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of a Novel Brain-Computer Interface Neuromodulative Intervention to Relieve Neuropathic Pain Following Spinal Cord Injury: Protocol for a Single-Case Experimental Design With Multiple Baselines

Abstract: Background Neuropathic pain is a debilitating secondary condition for many individuals with spinal cord injury. Spinal cord injury neuropathic pain often is poorly responsive to existing pharmacological and nonpharmacological treatments. A growing body of evidence supports the potential for brain-computer interface systems to reduce spinal cord injury neuropathic pain via electroencephalographic neurofeedback. However, further studies are needed to provide more definitive evidence regarding the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The targeted frequency bands are extracted and processed in real time, then their calculated power is presented to the individual as a form of positive or negative reinforcement [11,17]. Examples of such reinforcement include advancement or setbacks in a video game, and positive/negative visual and auditory feedback [18,19]. Different EEG neurofeedback techniques train individuals with chronic pain to gain control over their abnormal brain activity, which ultimately leads to pain reduction [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The targeted frequency bands are extracted and processed in real time, then their calculated power is presented to the individual as a form of positive or negative reinforcement [11,17]. Examples of such reinforcement include advancement or setbacks in a video game, and positive/negative visual and auditory feedback [18,19]. Different EEG neurofeedback techniques train individuals with chronic pain to gain control over their abnormal brain activity, which ultimately leads to pain reduction [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such reinforcement include advancement or setbacks in a video game, and positive/negative visual and auditory feedback [18,19]. Different EEG neurofeedback techniques train individuals with chronic pain to gain control over their abnormal brain activity, which ultimately leads to pain reduction [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Building on these findings, a hypnosis-enhanced cognitive therapy intervention (HYP-CT) was developed to target negative thoughts about chronic pain for people with disabilities and chronic pain. Initial pilot studies and follow-up clinical trials have consistently found HYP-CT to be effective, resulting in a marked reduction in pain intensity compared to pain education, CT, or hypnosis alone [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%